The Experimental Study of Adsorption of Ni (Ii) From Aqueous Solution Using Chelating Schiff’s Base Derived From 2-Aminobenzoic Acid and Benzoin - Ibrahim Jimoh; Abdullahi Jimoh (Genius Journals, 2021)
The adsorption of nickel from aqueous solution using chelating Schiff’s base derived from 2-aminobenzoic acid and benzoin was studied. The prepared Schiff base resin was characterized by means of Fourier Transform Infrared Spectroscopy (FTIR) and Atomic Absorption Spectroscopy (AAS) was used to determine its concentration. The bands at 3378 cm-1 and 1680 cm-1 of Schiff base shows the presence of O-H and the C=N group respectively while the shift in the Schiff base peaks at 3413 and 1681cm-1 indicates adsorption. The adsorption kinetics studies were investigated using 0.5g of Schiff base in 10 mg/L solutions of Nickel (ll) ions under previously obtained optimized conditions. The maximum adsorption of Nickel (ll) ions by Schiff’s base derived from 2- aminobenzoic and benzoin was 97.7% within initial concentration of 10mg/L and the removal rate of 97.7% was also within 90 minutes. The kinetic studies showed that the removal of Nickel (ll) ions correlated well with the pseudo second-order kinetic model indicating chemical adsorption and the adsorption capacity of Schiff base was 4.89mg/g for Nickel (ll) ions and it possess monolayer and as well found to be fitted into Langmuir Isotherm
Keywords: Adsorption; chelating Schiff bases; 2-aminobenzoic acid and benzoin